Analisis efektivitas dan efisiensi penerapan face recognition boarding pass di Stasiun Yogyakarta dan Solo Balapan - Iswanto, Ary Putra; Azar, Mochammad; Darmawan, Endras Setyo; Puspitasari, Mariana Diah (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
The need for comfort and convenience in everyday life is increasing along with the times. In the transportation sector, especially railways, facial recognition technology has brought significant changes. PT Kereta Api Indonesia (PT KAI) has implemented a face recognition-based boarding pass system at 11 stations. With the implementation of this technology, PT KAI strives to provide better service to passengers and meet the needs of increasingly advanced technology to improve the effectiveness and efficiency of the boarding process at train stations. This study aims to analyze the effectiveness and efficiency of the implementation of face recognition boarding passes at Yogyakarta Station and Solo Balapan Station. The method used in this study is effectiveness analysis by Ndraha and efficiency analysis with Data Envelopment Analysis (DEA). The results of the study for effectiveness explain that Yogyakarta Station and Solo Balapan Station average 86.34% for Yogyakarta Station and 86.37% for Solo Balapan Station. Yogyakarta Station is declared efficient with a score of 100% and Solo Balapan Station is not yet efficient with a score of 80%.